FAKTOR-FAKTOR STRUKTUR MODAL MENURUT TRADE OFF THEORY - Farah Tri Megawati; Nana Umdiana; Lulu Nailufaroh (Faculty of Economics and Business, 2021)
This study purposed to examine the effect of Corporate tax rate and Non debt tax shield on their Capital Structure according to Trade Off Theory on manufacturing companiessubsector metal and allied product that listed in Indonesia Stock Exchange for period 2016-2019. The study was conducted uing quantitative methods with an associative approach. The study population numbered 16 companies and 6 companies were sampled using purposive sampling. The study was conducted at manufacturing companies subsector metal and allied product that listed in Indonesia Stock Exchange for period 2016-2019. Classic assumption test using the test for normality, multicollinearity, autocorrelation, and heteroscedasticity. The regression analysis used is multiple linear regression analysis. Data was collected with the Financial Statement 2016-2019 and analyzed with IBM SPSS version 25. The results of this study indicate that the use of high debt to obtain a low corporate tax rate can cause a high risk for the company to go bankrupt, so the company prefers to use depreciation costs to obtain tax savings. If the depreciation cost of the company is high, the company can also reduce the use of debt. This shows that the higher the capital structure, the lower the corporate tax rate obtained by the company and the higher the NDTS, the lower the capital structure. In this study, there are still many limitations and shortcomings namely the influence of the independent variable on the dependent variable can only explain by 63,2%.